ANALISIS PENGELOLAAN PELABUHAN PERIKANAN PANTAI PASONGSONGAN KABUPATEN SUMENEP UNTUK PENINGKATAN PRODUKSI PERIKANAN TANGKAP - Ruhah Ruhah; Sugiono Sugiono; Doni Ferdiansyah (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2022)
Iincreased capture fisheries production at UPT. P3 Pasongsongan is supported by an increase in the number of visiting ships. This in crease in productionmust bebalanced whit proper management. The porpose of this study was to determine the condition of the facilities at UPT. P3 Pasongsongan, knows the management of activities and facilities at UPT. P3 Pasongsongan, and analyzes the right strategy to be applied in the management of P3 Pasongsongan, so that it can provide useful outputs for all aspects related to P3 Pasongsongan. The method used in this research is descriptive method with SWOT analysis to identify various factors in order to formulate a good and appropriate management strategy.based on the results of the analysis that the existing facilities at UPT. P3 pairs are in good condition and still suitable for use, likewise the activities starting from fish marketing, fish processing, and fish marketing are going well, the only constraints are that TPI is not good and ther is no coold storage that can hinder activities in UPT. P3 Psongsongan. While the SWOT anlysis obtained is the result of imlementing the S-O strategy (Streght-Opportunity) which in its applications uses strength to take advantage of opportunities.